Three distinct clones of carbapenem-resistant Acinetobacter baumannii with high diversity of carbapenemases isolated from patients in two hospitals in Kuwait - N.A. Al-Sweih; M. Al-Hubail; V.O. Rotimi (Elsevier, 2012)
Summary: Objectives: This study was undertaken to investigate the clonal relatedness of multidrug-resistant (MDR) Acinetobacter baumannii isolates collected from patients in two teaching hospitals in Kuwait. Materials and methods: Clinically significant consecutive isolates of A. baumannii obtained from patients in the Mubarak (36) and Adan (58) hospitals over a period of 6 months were studied. These isolates were identified using molecular methods, and their antimicrobial susceptibility was determined by the Etest method. The mechanism of resistance to carbapenem was investigated by PCR, and pulsed-field gel electrophoresis (PFGE) was used to determine the clonal relatedness of MDR isolates. Results: Of the 94 isolates investigated, 80 (85.1%) were multidrug resistant (MDR). The A. baumannii PFGE clone A and subclone A1 were the most prevalent in patients infected with MDR isolates. Fifty-five (94.8%) and 15 (41.7%) of the MDR isolates from the Adan and Mubarak hospitals, respectively, belonged to PFGE clone A; isolates in this group showed higher resistance rates to antibiotics than isolates form other groups. Of the 94 isolates, 40 (42.6%) were resistant to either imipenem or meropenem or to both (CRAB). Most CRAB isolates (29/40 or 72.5%) carried bla genes, which code for MBL (VIM-2 and IMP-1) enzymes. Two isolates harbored blaOXA-23. Conclusion: Three distinct clones of CRAB were isolated, providing evidence of a high diversity of carbapenemases among our geographically related isolates. Keywords: MDR A. baumannii, Genotypes, bla genes, Kuwait hospitals